Behavior and Identity of Flirting of Students a University - Khaenamkew, Daycho; Muhamad, Chettha; Katasomboon, Hathaichanok; Atcharoek, Benyapa; Sodphasert, Sanya; Jantawong, Ladawan (Academic and Research Journal of Liberal Arts (Online), 2021)
This article aims to study: (1) Behavior of Flirting of Students. (2) Identity of Flirting of Students. The research was conducted by mixed methods; Questionnaires were used to collect data from 26 Student. The data were analyzed using frequency, percentage, mean and standard deviation. Furthermore, qualitative information from interviews and observation record with 10 key purposing informants; Students, Parents and Teachers. The data were analyzed using descriptive analysis. The findings revealed as follows: (1) Behavior of Flirting of Students: the sensitive, the single, the declaration of love, The Good-natured, and the crimping side in all aspects with moderate level ( = 3.18, S.D. = 1.31). The aspect with the highest mean was the sensitive with moderate level ( = 3.41, S.D. = 1.30), next is the declaration of love with moderate level ( = 3.40, S.D. = 1.38), the crimping side with moderate level ( = 3.19, S.D. = 1.31), the Good-natured with moderate level ( = 3.14, S.D. = 1.47), and the single with moderate level ( = 3.01, S.D. = 1.31). (2) Identity of Flirting of Students: they are met good looking people, they will say they are single and flirt immediately, they are cared for to have a special feeling to “dedicated”, to makes you feel like you fall in love, until having to “Make Love” to modify the relationship between lovers. After sexually and if pregnant, it is not responsible. And break up and find new ones to replace the old ones to “Abandonment." Indicate the findings in the form of “Dedicated, Make Love (Abortion), and Abandonment." These are valued that arise today, and create a social problem in the future.